Reversion of down-regulation of intestinal multidrug resistance-associated protein 2 in fructose-fed rats by geraniol and vitamin C: Potential role of inflammatory response and oxidative stress - Zecchinati, Felipe (2019)
Intestinal multidrug resistance-associated protein 2 is an ABC transporter that limits the absorption of xenobiotics ingested orally, thus acting as essential component of the intestinal biochemical barrier. Metabolic Syndrome (MetS) is a pathological condition characterized by dyslipidemia, hyperinsulinemia, insulin resistance, chronic inflammation, and oxidative stress (OS). In a previous study we demonstrated that MetS-like conditions induced by fructose in drinking water (10% v/v, during 21 days), significantly reduced the expression and activity of intestinal Mrp2 in rats. We here evaluated the potential beneficial effect of geraniol or vitamin C supplementation, natural compounds with anti-inflammatory and anti-oxidant properties, in reverse fructose-induced Mrp2 alterations. After MetS-like conditions were induced (21 days), animals were cotreated with geraniol or vitamin C or vehicle for another 14 days. Decreased expression of Mrp2 protein and mRNA due to fructose administration was reversed by geraniol and by vitamin C, consistent with restoration of Mrp2 activity evaluated in everted intestinal sacs. Concomitantly, increased intestinal IL-1β and IL-6 levels induced by fructose were totally and partially counterbalanced, respectively, by geraniol administration. The intestinal redox unbalance generated by fructose was improved by geraniol and vitamin C, as evidenced by decreasing lipid peroxidation products and activity of Superoxide Dismutase and by normalizing glutathione reduced/oxidized glutathione ratio. The restoration effects exhibited by geraniol and vitamin C suggest that local inflammatory response and OS generated under MetS-like conditions represent important mediators of the intestinal Mrp2 down-regulation. Additionally, both agents could be considered of potential therapeutic value to preserve Mrp2 function under MetS conditions.